Mechanisms Underlying Curcumin-Induced Neuroprotection in Cerebral Ischemia - Fan, Feng; Lei, Meng (Frontiers in Pharmacology, 2022)
Ischemic stroke is the leading cause of death and disability worldwide, and restoring blood flow to ischemic brain tissues is currently the main therapeutic strategy. However, reperfusion after brain ischemia leads to excessive reactive oxygen species production, inflammatory cells recruitment, the release of inflammatory mediators, cell death, mitochondrial dysfunction, endoplasmic reticulum stress, and blood-brain barrier damage; these pathological mechanisms will further aggravate brain tissue injury, ultimately affecting the recovery of neurological functions. It has attracted the attention of researchers to develop drugs with multi-target intervention effects for individuals with cerebral ischemia. A large number of studies have established that curcumin plays a significant neuroprotective role in cerebral ischemia via various mechanisms, including anti-oxidation, anti-inflammation, anti-apoptosis, protection of the blood-brain barrier, and restoration of mitochondrial function and structure, resultantly restoring cerebral circulation, reducing infarct volume, improving brain edema, promoting blood-brain barrier repair, and improving neurological functions. Therefore, summarizing the results from the latest literature and identifying potential mechanisms of action of curcumin in cerebral ischemia will serve as a basis and guidance for clinical applications of curcumin in the future.